Compatibility and high temperature performance of recycled polyethylene modified asphalt using molecular simulations. Issue 13 (2nd September 2021) - Yu, Caihua; Hu, Kui; Chen, Yujing; Zhang, Wengang; Chen, Yan; Chang, Rong
ABSTRACT: The objective of this study was to explore the interaction mechanism between recycled polyethylene (RPE) and base asphalt to reveal the microscopic mechanism of the two–phase structure formation, separation, and high–temperature stability of RPE–modified asphalt. Density functional theory (DFT) and molecular dynamics (MD) simulations were used to explore the interaction of RPE–modified asphalt at the atomic and molecular scales, and the simulation results were verified by fluorescence microscopy and dynamic shear rheology experiments. The results show that the binding energy of RPE with light components (aromatics and saturates) (730–1030 Ha) was smaller than that of asphaltenes with light components (2750–4330 Ha) in the following order of magnitude: phenol > pyrrole > thiophene > RPE. The charge transfer numbers of RPE with asphalt molecules indicate that RPE interacted weakly with asphaltenes and resins. In addition, MD simulation results show that RPE elevates the diffusion coefficient of asphalt molecules. The two–phase structure of RPE–modified asphalt was observed using fluorescence microscopy, and the RPE phase became larger with increasing development time. The dynamic shear rheology experiment results show that RPE reduced the damping factor while enhancing the complex modulus and rutting factor of asphalt.